Perforator flaps in soft tissue reconstruction: clinical outcomes in reconstructive plastic surgery - Charleston, Manuel Cabrera; Oscura Paredes, Daniela Guadalupe; Lara Sanchez, Miguel Angel (International Journal of Research in Medical Sciences, 2025)
Perforator flaps constitute a significant advancement in soft tissue reconstruction within reconstructive plastic surgery, relying on perforator vessels that supply the skin and subcutaneous tissue without requiring large muscle or fascia volumes. This innovative approach allows for more refined and less invasive reconstructions, preserving muscular integrity and reducing functional deficits at the donor site. These flaps have become increasingly important in the management of complex defects resulting from oncologic resections, traumatic injuries, or chronic wounds particularly in anatomically complex regions. Advances in preoperative imaging and intraoperative navigation have enhanced the accuracy of flap planning and reduced complication rates. Additionally, the evolution of flap design-such as propeller, free-style, and supermicrosurgical flaps-has expanded reconstructive options. This systematic review aimed to evaluate recent innovations, surgical techniques, and clinical outcomes associated with perforator flaps across a range of reconstructive scenarios. A total of 30 studies were included, comprising clinical trials and observational research focusing on different anatomical sites (extremities, head and neck, breast, and trunk). The findings reveal a flap survival rate ranging from 93% to 98%, lower complication rates compared with conventional musculocutaneous methods, and high patient satisfaction. Nevertheless, heterogeneity in outcome measures and lack of randomized studies with large sample sizes underscore need for more standardized protocols and multicenter research to draw stronger conclusions.